Aktualisasi Program Modal Usaha oleh PNM (Permodalan Nasional Madani) Mekar terhadap Pemberdayaan Perempuan di Nagari Surantih Kecamatan Sutera Kabupaten Pesisir Selatan - Mahyuni, Eling; Azwar, Azwar; Rahmat, Indra (Asian Journal of Science, Technology, Engineering, and Art, 2023)
The actualization of Mekar's National Madani Capital Program (PNM) is to provide group-based empowerment services for women micro entrepreneurs, through improving financial management to achieve family goals and prosperity. The purpose of this study is to describe the implementation and factors that influence the implementation of the Mekar national civil capital (PNM) program for the community in Nagari Surantih, Sutera sub-district, Pesisir Selatan district. The theory used in this study is the functional structural theory put forward by Talcot Parson. The type of research used is qualitative research with a descriptive type, the research was conducted in Nagari Surantih, Sutera sub-district, Pesisir Selatan district. Using primary data sources and secondary data. The informants in this study were Mekar's National Civil Capital Officer (PNM), Wali Nagari, social welfare development section, community, chairman and members of the PNM Mekar group. Data collection techniques in this study using observation techniques, interviews, and documentation. The data analysis technique in this study was to use the Miles and Huberman interactive model which consisted of four stages: data collection, data reduction, data presentation, and drawing conclusions or verification. The results of the study found that there was an implementation of the Blooming National Madani Capital (PNM) program in Nagari Surantih when applying for a Blooming National Civil Capital (PNM) loan, there were several conditions that had to be met first. There is to conduct surveys related to businesses that will be opened or are being run, this is done to avoid misuse of capital loans. The disbursement of capital must be used according to what has been agreed in the agreement to start a business. There is installment financing that is carried out in weekly group meetings (PKM) or meetings. There are supporting factors for policies from the government, easy application requirements and can be accessed by women. Mekar's Civil National Capital Program (PNM) seeks to prevent it from becoming involved in moneylender debts, the trust of both parties, installment financing is carried out on a group responsibility basis. There is a barrier factor. National Civil Capital only provides services for women, while men also need business capital to do work. Based on the results of the research above, it can be concluded that the implementation of the Mekar National Civil Capital (PNM) program involved the submission of requirements that were met first, conducting a survey, disbursing business capital, and financing installments of business capital loans by Mekar's civil national capital (PNM). Supporting factors that influence the implementation of Civil National Capital are government policies, submissions whose conditions are not onerous, PNM Mekar prevents loan sharks from loan sharks, trust from both parties, installment financing is carried out by the collective responsibility of the group, inhibiting factors PNM Mekar only provides business capital loan services for women.